Interference of two pulse-like spatial beams with arbitrary transverse separation. (11th November 2016) - Flórez, Jefferson; Álvarez, Juan-Rafael; Calderón-Losada, Omar; Salazar-Serrano, Luis José; Valencia, Alejandra
Abstract: We report the observation of interference in position and transverse momentum variables between two parallel-propagating Gaussian beams separated by an arbitrary distance. This resembles the Alford and Gold effect that has been reported for the time-frequency degree of freedom, and constitutes a method for spatial intensity shaping of light beams. We observe this interference by using a tunable beam displacer, which plays the role of a Michelson interferometer for the transverse spatial variables. Additionally, we employ the interference pattern as a function of the separation between the beams to determine the spatial coherence length of the original beam.